Effects of substrate bias voltage on properties of CoCrTa/Cr media - Kim, SH; Shin, KH; Lee, TD (ELSEVIER SCIENCE SA, 1999)
CoCrTa/Cr thin films were deposited on NiP/AlMg and glass substrates by a DC magnetron sputtering method with a DC substrate bias voltage ranging from 0-500 V. The changes of magnetic properties, orientation of grains and the composition of CoCrTa were investigated. Three different kinds of biasing schemes were used. In group A, the substrates were biased during Cr underlayer deposition and the subsequent CoCrTa layers were deposited without bias. In group B, Cr underlayers were deposited without bias and the subsequent substrates were biased during the CoCrTa layer deposition. In group C, the two layers were biased. In all cases, coercivity increased to a maximum value at the bias voltage of 300 V and decreased with further increasing the bias voltage. When the Cr underlayer was deposited on mechanically textured (scratched) NiP substrates with the substrate biased condition, smaller and more uniform column size distribution were obtained and clear texture lines were observed in comparison to the unbiased specimens. The smaller Cr column size subsequently induces smaller Co grains. This may be main cause of the coercivity increase in the group A specimens. When the CoCrTa layer was deposited with higher bias voltage, the composition of the Blm changes due to different resputtering rate and Cr segregation is more enhanced. These two effects are contributing to the increase of the CoCrTa coercivity. Orientation ratio (OR) of Hc in circumferential and radial direction was also studied as a function of the bias voltage. The origin of coercivity OR was also discussed. (C) 1999 Elsevier Science S.A. All rights reserved.
Keywords: THIN-FILM MEDIA; SPUTTERED COCR/CR; MICROSTRUCTURE; ANISOTROPY; TEXTURE